2015
DOI: 10.1371/journal.pone.0132938
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the UCP2 Gene Are Associated with Glomerular Filtration Rate in Type 2 Diabetic Patients and with Decreased UCP2 Gene Expression in Human Kidney

Abstract: IntroductionUncoupling protein 2 (UCP2) reduces production of reactive oxygen species (ROS) by mitochondria. ROS overproduction is one of the major contributors to the pathogenesis of chronic diabetic complications, such as diabetic kidney disease (DKD). Thus, deleterious polymorphisms in the UCP2 gene are candidate risk factors for DKD. In this study, we investigated whether UCP2 -866G/A, Ala55Val and Ins/Del polymorphisms were associated with DKD in patients with type 2 diabetes mellitus (T2DM), and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 51 publications
3
34
1
Order By: Relevance
“…As ROS production contributes to mitochondrial dysfunction in AKI and diabetic nephropathy, UCP2 has been explored in the kidney and in these disease states 38 . Studies investigating the role of UCP2 polymorphisms in the kidney that exacerbate disease in patients with diabetic nephro pathy reveal that UCP2 is a potential target for treatment 39 . Lack of UCP2 has also been shown to worsen tubular injury after induction of experimental AKI in mice 38 .…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…As ROS production contributes to mitochondrial dysfunction in AKI and diabetic nephropathy, UCP2 has been explored in the kidney and in these disease states 38 . Studies investigating the role of UCP2 polymorphisms in the kidney that exacerbate disease in patients with diabetic nephro pathy reveal that UCP2 is a potential target for treatment 39 . Lack of UCP2 has also been shown to worsen tubular injury after induction of experimental AKI in mice 38 .…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Consistent with the role of UCP2 in decreasing oxidative stress, several studies have suggested that polymorphisms in the UCP2 gene are associated with ROS-related pathologies (Ji et al, 2004;Yu et al, 2009;Chai et al, 2012) and with the development of DM and its chronic complications (Jia et al, 2009;Crispim et al, 2010;de Souza et al, 2012de Souza et al, , 2013de Souza et al, , 2015. To date, three common UCP2 polymorphisms have been well studied: the functional -866G/A polymorphism (rs659366) in the promoter region; the Ala55Val polymorphism (rs660339) in exon 4, and the 45 bp insertion/deletion (Ins/Del) polymorphism in the 3' untranslated region (Jia et al, 2009;Dalgaard, 2011).…”
Section: Introductionmentioning
confidence: 68%
“…The -866G/A and the Ala55Val polymorphisms were in almost complete linkage disequilibrium in our population from the South of Brazil (Crispim et al, 2010). Recently, we reported that the polymorphic -866A/55Val/Ins haplotype was also an independent risk factor for DKD (OR = 2.14, 95% CI 1.04 -4.40) in patients with type 2 diabetes mellitus (T2DM) (de Souza et al, 2015). Moreover, T2DM patients carrying the polymorphic haplotype showed lower estimated GFR compared with patients carrying the reference haplotype (-866G/Ala55/Del).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations